The use of a candidate gene approach to study Botrytis cinerea resistance in Gerbera hybrida - Fu, Yiqian; Song, Yin; van Tuyl, Jaap M.; Visser, Richard G. F.; Arens, Paul (Frontiers in Plant Science, 2023)
Candidate genes (CG) for Botrytis cinerea resistance described in literature were mapped on gerbera linkage maps for which several QTL for botrytis resistance had been found previously using a rapid, low-cost platform for SNP genotyping. In total, 29 candidate genes were mapped in either of two mapping populations. Four CGs were mapped within the previous identified QTL intervals and three co-localized with QTL. Two of these candidate genes for resistance against B. cinerea, PG1 (polygalacturonase gene) and sit (sitiens, ABA-aldehyde oxidase gene) that mapped in QTL regions for the ray floret disease resistance test were studied in detail. Virus-induced gene silencing (VIGS) was used to characterize gene function in relation to botrytis resistance. Results showed a significantly delayed growth of lesions upon botrytis infection on VIGS candidate gene silenced ray florets compared to controls. Combining QTL analysis, candidate gene mapping and VIGS showed to be an useful combination to identify possible causal genes and for understanding the molecular mechanisms of Botrytis resistance in gerbera. The two genes seem to act as partial S-genes and are likely among the determining genes leading to the variation observed for B. cinerea resistance in gerbera.